Long-term economic and social outcomes of youth suicide attempts. (February 2022) - Orri, Massimiliano; Vergunst, Francis; Turecki, Gustavo; Galera, Cédric; Latimer, Eric; Bouchard, Samantha; Domond, Pascale; Vitaro, Frank; Algan, Yann; Tremblay, Richard E.; Geoffroy, Marie-Claude; Côté, Sylvana M.
Abstract : Background: Youth who attempt suicide are more at risk for later mental disorders and suicide. However, little is known about their long-term socioeconomic outcomes. Aims: We investigated associations between youth suicide attempts and adult economic and social outcomes. Method: Participants were drawn from the Quebec Longitudinal Study of Kindergarten Children ( n = 2140) and followed up from ages 6 to 37 years. Lifetime suicide attempt was assessed at 15 and 22 years. Economic (employment earnings, retirement savings, welfare support, bankruptcy) and social (romantic partnership, separation/divorce, number of children) outcomes were assessed through data linkage with government tax return records obtained from age 22 to 37 years (2002–2017). Generalised linear models were used to test the association between youth suicide attempt and outcomes adjusting for background characteristics, parental mental disorders and suicide, and youth concurrent mental disorders. Results: By age 22, 210 youths (9.8%) had attempted suicide. In fully adjusted models, youth who attempted suicide had lower annual earnings (average last 5 years, US$ −4134, 95% CI −7950 to −317), retirement savings (average last 5 years, US$ −1387, 95% CI −2982 to 209), greater risk of receiving welfare support (risk ratio (RR) = 2.05, 95% CI 1.39 to 3.04) and were less likely to be married/cohabiting (RR = 0.82, 95% CI 0.73 to 0.93), compared with those who did not attempt suicide. Over a 40-year working career, the loss of individual earnings attributable to suicide attempts was estimated at US$98 384. Conclusions: Youth who attempt suicide are at risk of poor adult socioeconomic outcomes. Findings underscore the importance of psychosocial interventions for young people who have attempted suicide to prevent long-term social and economic disadvantage.